Profil Penalaran Siswa SMA dalam Menyelesaikan Masalah Geometri ditinjau dari Perbedaan Gender - Hamdi, Rajib Syahrul; Lukito, Agung; Manoy, Janet Trineke (LP. Ma'arif Janggan Magetan, 2024)
Reasoning profile is description of the process of logical thinking in solving mathematical problems related to determining a conclusion using the knowledge possessed in the cognitive structure. The indicators used to reveal the profile of reasoning include understanding the problem, making a settlement plan, carrying out the settlement plan, and looking back at the results that have been resolved. Geometry is a part of mathematics that discusses the shape and size of an object that has a certain regularity. Geometry problems are problems in the form of geometry (three dimensions) for which routine procedures are not available for solving. Meanwhile, gender differences affect the reasoning profess in solving geometric problems. This study aims to describe the reasoning profiles of high school students with masculine male and feminine gender in solving geometric problems. This descriptive research with a qualitative approach was carried out in class XI of SMA Negeri 1 Sidayu in the 2022/2023 academic year. The subjects of this study were two students of class XI who had equal mathematical abilities. Data collection was carried out by in-depth subject interviews based on the Geometry Problem Solving Task. Geometry Problem Solving Tasks in the form of description geometry questions. In collecting data using time triangulation techniques to obtain credible data. Data analysis was carried out by condensing data, presenting data, and drawing conclusions. The results showed that masculine male students used logical thinking in solving problems with a more analytical nature in giving appropriate arguments. Whereas feminine women use logical thinking in solving problems but in giving arguments they are less analytical. This shows that the reasoning profile of masculine boys in solving geometry problems is better than feminine girls. Differences in reasoning profiles result in students' abilities in mathematical activities will havetesi an impact on student learning outcomes.